A Cultural Approach to Populism - Herkman, Juha (Taylor & Francis, 2022)
This book is a critical introduction of theorisations and research on contemporary political populism emphasising the cultural perspective. It introduces the basic theories and analyses the cultural construction of populism regarding radical democratic theory and empirical studies. Applying Ernesto Laclau's and Chantal Mouffe's theories, the author builds a bridge between radical democratic and ideational approaches on populism with examples and studies that emphasise European radical right populism, alongside the United States, Latin American and Asian cases. Special attention is paid to relationships between populism and democracy and between populism and media. The contemporary appeal of populism is linked to current developments in welfare states and in global economic and cultural trends. The future of populism is discussed in regard to COVID-19 pandemic and Donald Trump's fall in the US presidential elections in 2020 that together with abovementioned global megatrends and with the development of media and communication environment set conditions for the 2020s populism. Scholars and students of political science, media and communication studies, cultural studies and social sciences will find this a unique and novel approach.